Cloud computing for dynamic systems. (1st January 2011) - Sabry, Khaled
Cloud computing is a fast emerging model for enabling dynamic on-demand computing and IT-based services. It promotes dynamic properties and characteristics such as scalability, agility, flexibility, virtualised and distributed on-demand computing. However, embracing this model requires careful and full understanding, analysis and evaluation of the technology, opportunities and challenges that may be encountered. This paper reviews literature, explores and discusses the notion of cloud computing as part of a continuous research in the areas of dynamic and interactive information systems. It proposes the CCM model that represents the main components and characteristics of cloud computing for dynamic systems. It concludes with a reflection on the future of cloud computing and future research.